VIRTUAL REALITY OR REALITY: CONTENT IS ALWAYS KEY TO ENJOYMENT, UNDERSTANDABILITY AND COMPREHENSION. Issue 2 (3rd April 2022) - Bauer, Steven; Fischbach, Sarah; Labban, Alice; Fleck, Emilie M; Speth, Anna Mauldin
ABSTRACT: This article presents a new approach to bring virtual reality into the marketing classroom. Our study adds to the literature by testing two different types of virtual reality content and showing the importance of content in producing desired educational outcomes. We also extend past research by suggesting specific processes and resources for adapting virtual reality to the marketing curriculum. Virtual reality has not been widely applied to core marketing curriculum, particularly global marketing. The medium is especially suited to global marketing, since success in the area depends on understanding foreign environments. Our new approach uses two types of virtual reality videos, an educational video on South Sudan and advertisement for Toms Shoes, to teach global marketing concepts. We investigate the impact of this approach in a study with 100 students and find that the VR vs. non-VR format has a significantly positive impact on enjoyment. In addition, the Toms VR video scores significantly higher than the South Sudan VR video on enjoyment, content understandability, and comprehension. Our results point to the importance of content in creating educational materials in any format, and suggest a particular need to develop virtual reality materials which align with learning objectives in the marketing curriculum.